IDENTIFYING RELATIONSHIP INVOLVING LEARNING STYLES AND PROBLEM SOLVING SKILLS AMONG VOCATIONAL STUDENTS - Mohamad, Mimi Mohaffyza; Heong, Yee Mei; Rajuddin, Muhammad Rashid; Keong, Tee Tze (Journal of Technical Education and Training, 2011)
The purpose of this study was to determine the relationship between students’ learning styles and problem solving skills among students in Building Construction Course at Vocational School. This study also investigated the differences between the students’ type of learning styles and their ability to solve the problem using their creative thinking. A survey was carried out on 68 vocational students in Building Construction Course from two Vocational Schools. Felder-Soloman’s Index of Learning Styles (ILS) and elements of creative thinking in problem solving for Vocational Education were the tools used in this study. Creative thinking in problem solving elements was categorized from the subject specification used in Building Construction curriculum. In brief, the ILS have five dimension; Processing, Perception, Input, Understanding and Perception. The results show that the Input style dominates the learning styles of Building Construction’s students in Vocational School and manipulating idea is the dominant creative thinking elements to solve the problem which students preferred. In conclusion, type of students’ learning styles will influence how they can cater their learning to improve their academic achievement and how they can use their creativity to solve the problem in actual situation in Building Construction work. However, learning styles are not main indicator to predict how students excellent are.